The influence of referential accessibility in the usage of personal subject and object pronouns in conversational spanish - García Salido, Marcos (Boletín de Filología, 2008)
Spanish personal (tonic) pronouns have been considered an emphatic version of the affixal and unstressed personal markers. It has been claimed that personal pronouns are focused units and have contrastive value, which is not easy to fi nd in every pronominal occurrence from a conversational sample. Referential accessibility, a factor that influences the coding of referential expressions, can account for those cases where personal pronouns alternate between unstressed personal forms and which cannot be explained by means of contrastiveness or focalization.